2018
DOI: 10.3390/atmos9060232
|View full text |Cite
|
Sign up to set email alerts
|

PM1 Chemical Characterization during the ACU15 Campaign, South of Mexico City

Abstract: Abstract:The "Aerosoles en Ciudad Universitaria 2015" (ACU15) campaign was an intensive experiment measuring chemical and optical properties of aerosols in the winter of 2015, from 19 January to 19 March on a site in the south of Mexico City. The mass concentration and chemical composition of the non-refractory submicron particulate matter (NR-PM 1 ) was determined using an Aerodyne Aerosol Chemical Speciation Monitor (ACSM). The total NR-PM 1 mass concentration measured was lower than reported in previous cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Afterwards, Table I presents mean, median, and standard deviations for the determined concentrations, for the three campaigns. While the 2015 basic statistics complement the results given by Salcedo et al (2018), the 2016 statistics has been described previously (Hernández-López et al 2016, Hernández-López et al 2018. The PM 2.5 official Mexican standard (SSA 2014) was never exceeded in 2015 and 2016.…”
Section: Chemical Analyses Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Afterwards, Table I presents mean, median, and standard deviations for the determined concentrations, for the three campaigns. While the 2015 basic statistics complement the results given by Salcedo et al (2018), the 2016 statistics has been described previously (Hernández-López et al 2016, Hernández-López et al 2018. The PM 2.5 official Mexican standard (SSA 2014) was never exceeded in 2015 and 2016.…”
Section: Chemical Analyses Resultssupporting
confidence: 64%
“…The details of the 2015 campaign are thoroughly described by Salcedo et al (2018). The samples were collected during dry-winter season, from January 16 to March 26, 2015, daily from 8:00 h to 7:00 h of the next day (23 h), including weekends, during the whole campaign.…”
Section: Sampling Periods and Proceduresmentioning
confidence: 99%
“…Another field study conducted from January to March of 2015 showed that the PM 1 mass concentration measured in the south side of the city was lower than those measured in the north and east sides; the aerosols were also more aged, consistent with the location of the PM sources and their precursors in the city, as well as the meteorological patterns [52]. These findings point out that the formation of secondary aerosols might have a substantial spatial variability that needs to be further investigated.…”
Section: Ambient Particulate Mattermentioning
confidence: 82%
“…Currently, emissions are relatively well controlled for large industries, but not for the medium, small, and micro industries. However, the large industrial Tula-Tepeji corridor, located about 70 km northwest of the MCMA center, is still the main source of SO 2 and particulate sulfate in Mexico City [51,52].…”
Section: Reduction Of Emissions In Industries and Servicesmentioning
confidence: 99%
“…The mean contribution of HOA-2 to OA was 18% (2.5 μg m −3 ), with a daily peak concentration of 5.4 μg m −3 , while its mean contribution was the highest among components for winds of the SW-NW sector (28%). The combined fraction of the two HOA components was 30% (Figure 6a), which is a large fossil fuel combustion contribution compared to other urban locations [122][123][124][125], but nevertheless reasonable, considering the central placement of the site in a particle pollution hotspot. HOA-2: While the profiles of HOA-2 and HOA-1 had similar main features (i.e., primary hydrocarbon fragments), the former appears to be slightly more oxidized, with relatively enhanced contributions at m/z 44 and 18, most likely suggesting a longer atmospheric residence time compared to the more local HOA-1.…”
Section: Winter Periodmentioning
confidence: 70%